Induction of the sphingosine‐1‐phosphate signaling pathway by TGF‐β1 during Langerhans‐type dendritic cell differentiation. Issue 7 (19th April 2021) - Sconocchia, Tommaso; Del Gaudio, Ilaria; Meshcheryakova, Anastasia; Mechtcheriakova, Diana; Wadsack, Christian; Strobl, Herbert
Abstract : Gene profiling revealed that the S1P signaling pathway is induced by TGF‐β1 during LC commitment of monocytopoietic cells. Constitutive‐active TGF‐β1‐S1P signaling seems to elevate the activation threshold of LCs and thereby prevent inappropriate and overshooting immune responses to microbial and physicochemical environmental signals. In turn, signals that lead to LC migration may disrupt this pathway via inhibiting S1P bioavailability.